2020
DOI: 10.1088/1757-899x/960/3/032027
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcing of Sand With 3D Printed Fibres – Review of Properties, Fabrication of Fibres and Initial Testing Programme

Abstract: Fibre reinforcement is an effective method of soil improvement that presents an alternative solution to other more common methods of ground reinforcement, such as mechanical stabilization by geosynthetics (geogrids, geotextiles, geocomposites, etc.). Research activities in this area are being carried out, but the main disadvantage of currently used fibres is their uniform cross-section and usually smooth surface given by available production methods. This study presents an alternative way of fabrication of syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Geometric features of cells and stiffness of the geogrids were varied in plate load tests on sand reinforced with geogrids to suggest that a maximum bearing capacity ratio of 1.59 can be achieved through optimized cell dimensions. Chalmovsky et al [9] used 3D-printed synthetic fibres to reinforce clays. Drained triaxial tests on reinforced clays reinforced with 3D-printed fibres of varying shape showed that profiled fibres provide superior reinforcement than the straight fibres.…”
Section: Application Of 3d Printing In Geotechnical Engineeringmentioning
confidence: 99%
“…Geometric features of cells and stiffness of the geogrids were varied in plate load tests on sand reinforced with geogrids to suggest that a maximum bearing capacity ratio of 1.59 can be achieved through optimized cell dimensions. Chalmovsky et al [9] used 3D-printed synthetic fibres to reinforce clays. Drained triaxial tests on reinforced clays reinforced with 3D-printed fibres of varying shape showed that profiled fibres provide superior reinforcement than the straight fibres.…”
Section: Application Of 3d Printing In Geotechnical Engineeringmentioning
confidence: 99%